The Indirect Effect of Mindfulness in Marriage in the Relationship Between Digital Stress and Dyadic Adjustment: An Investigation of Dyadic Effects - Ceco, Gamze; Taskin, Sumeyye; Uygun, Ezgi Guney; Erus, Seher Merve; Satici, Seydi Ahmet (SPRINGER, 2025)
Studies on marriage make important contributions to the psychosocial health of individuals. In recent years, there are cases where the marital relationship has been negatively affected due to the use of social media. In this context, the concept of digital stress emerges as a current problem. We have less information about the mechanisms underlying the dyadic relationships of married individuals. This study reports the results of 325 married couples using actor-partner interdependence modeling. The mean age of women was 36.19 (SD = 7.83, range = 21-60) and the mean age of men was 39.12 (SD = 8.55, range = 24-67). Digital stress, mindfulness in marriage, and marital adjustment were measured among married individuals. According to the results, women's digital stress significantly predicted women's mindfulness in marriage. Similarly, men's digital stress significantly predicted women's mindfulness in marriage. Furthermore, women's mindfulness in marriage significantly predicted both women's and men's dyadic adjustment. Men's mindfulness in marriage also significantly predicted women's and men's dyadic adjustment. It was found that women's mindfulness in marriage has an indirect effect on the relationship between their digital stress and dyadic adjustment. In addition, men's mindfulness in marriage has an indirect effect on the relationship between their digital stress and dyadic adjustment. These findings indicate that digital stress plays a significant role in marital relationships, and mindfulness is one of the key mechanisms in these interactions. It is suggested that interventions aimed at increasing mindfulness in marriage could mitigate the negative effects of digital stress and strengthen dyadic adjustment in couples.
Keywords: Digital stress; Mindfulness in marriage; Dyadic adjustment; Married couples; MARITAL ADJUSTMENT; QUALITY; SCALE; INTELLIGENCE; TECHNOLOGY; COUPLES; Social Sciences - Other Topics